(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2023)
In recent decades, the medicinal values of traditional landraces have been of great interest and the cultivation is being revamped among the farmers of Tamil Nadu. The present investigation was aimed to analyse the phytonutrients, antioxidants and functional groups among the six traditional land races. Phytochemical analysis revealed that the pigmented traditional landraces of rice possessed more antioxidant properties. The traditional rice varieties, especially Mapillai samba was found to be superior in terms of moisture (11.5±0.16%) and total ash (1.71±0.14%), Kuzhiyadichan in protein (9.65±0.67%) and fat (2.53±0.17%), Iluppaipoo samba in carbohydrate (79.3±1.29) and energy (1525±24.8 kJ). Kuzhiyadichan had highest phosphorous (359±24.7), calcium (46.8±3.23), magnesium (135±9.30), iron (5.70±0.39) and zinc (2.70±0.19) content, whereas copper (0.353±0.02), manganese (0.965±0.06) and potassium (296±23.5) content was higher in Seeraga samba, Kichali samba and Mapillai samba, respectively. The studies revealed that Mapillai samba got the highest total phenols (39.25±0.88 mg), vitamin E (27.76±2.39), anthocyanins (45.2±0.16) and antioxidant activity (764±21.3) followed by Iluppaipoo samba among traditional rice varieties. FTIR analysis revealed the distribution of biochemically different phenols, carbohydrates, hydroxyl and amide groups. Traditional landraces can be used as a source of antioxidants and nutraceuticals. This finding confers new facet in rice breeding to develop a nutraceutical rich rice and to enhance the farmers production in order to meet the demand of food-based medicines.